Strategic alliances with suppliers and customers in a manufacturing supply chain: From a manufacturer's perspective - Loke Siew Phaik; Alan G. Downe; Murali Sambasivan (Emerald Group Publishing Limited, 2013)
Purpose – The main purposes of the study are to: test the strategic alliance framework developed by Sambasivan et al. on the strategic alliances with suppliers and customers, separately; and compare the factors influencing strategic alliances with suppliers and customers based on the results. The present study analyzes the effect of strategic alliance motives, environment, asset specificity, perception of opportunistic behavior, interdependence between supply chain partners, and relational capital on strategic alliance outcomes.